Osteoid Osteoma Masquerading as Cholelithiasis: A Case Report. Issue 1 (January 2020) - Fox, Michael A.; Berger, Ryan J.; Wright, Katherine A.; Lawrenz, Joshua M.; Sultan, Assem A.; Day, Carly; Farrow, Lutul D.; Ilaslan, Hakan; Mesko, Nathan W.
Abstract : Case: We present a case report of an 18-year-old woman who presented to a general surgeon with a several month history of intermittent right upper quadrant pain, strongly suggestive of symptomatic cholelithiasis and underwent a laparoscopic cholecystectomy. She was eventually found to have an osteoid osteoma (OO) of the right eighth rib. She was treated with radiofrequency ablation with complete resolution of symptoms 1 month after treatment. Conclusions: In cases where a patient's age and risk factors would make the diagnosis of cholelithiasis less likely, OO should be added to the differential diagnosis of symptomatic right upper quadrant pain.